Variations in the Vascular Anatomy of the Right Colon and Implications for Right-Sided Colon Surgery. Issue 3 (March 2017) - Kuzu, Mehmet Ayhan; İsmail, Erkin and Çelik, Safa and Şahin, Muhammed Feyzi and Güner, Mehmet Ali and Hohenberger, Werner and Açar, Halil İbrahim
Abstract : BACKGROUND: Knowledge of the normal pattern and variations of the blood supply of the right colon is crucial for better outcomes after colon surgery. OBJECTIVE: The purpose of this study was to describe the precise vascular anatomy of the right colon according to surgical perspective. DESIGN: Adult fresh cadavers were dissected between January 2013 and October 2015, focusing on the venous and arterial anatomy of the right side of the colon. SETTINGS: Macroscopic anatomical dissections were performed on 111 adult fresh cadavers with emphasis on the vascular anatomy of the right colon. The colic tributaries of the superior mesenteric artery and vein were documented in writing. Furthermore, the dissections were recorded with a video camera. RESULTS: The incidence of colic arteries arising from the superior mesenteric artery included ileocolic artery, 100%; right colic artery, 33.3%; middle colic artery, 100%; and accessory middle colic artery, 11, 7%. All 111 cadavers had a single ileocolic vein, which drained into the superior mesenteric vein in 103 cases (92.8%), into the gastro-pancreatico-colic trunk in 7 cases (6.3%), and into the jejunal trunk in 1 case (0.9%). The drainage site of the ileocolic vein to the superior mesenteric vein varied, and in 9% of cases the ileocolic vein did not accompany the ileocolic artery. The gastro-pancreatico-colic trunk was detected in 87 cases (78.4%); with several forms of the origin of the respective branches, the gastropancreatic trunk was detected in 24 cases (21.6), and the classic gastrocolic trunk of Henle was not detected. Variations were found in the formation and drainage routes of other venous colic tributaries of the superior mesenteric vein. LIMITATIONS: This study is limited by its use of cadavers in that it is impossible to trace each vessel to its origin in live surgery. CONCLUSIONS: Surgeons must watch, observe, and bear in mind that vascular variations can occur. Awareness of these complex variations may improve the quality of surgery and may prevent devastating complications during right-sided colon resections. Abstract : Supplemental Digital Content is available in the text.